Teacher's Role IDentifying and Overcoming Sex Bias in Classroom Management. Trainer Manual - Fair, Martha H.; Colorado State Dept. of Education, Denver ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1980)
Outlines are presented for teacher workshops on identifying and overcoming biased attitudes reflected in current literature and classroom instructional materials. Each session includes: (1) a needs assessment activity or exercise to express initial concerns; (2) a lecture introducing new concepts and activities; (3) activities providing an opportunity for participants to apply the concepts presented in the lecture; (4) activities designed to provide an opportunity to practice some skills necessary for the application of sex equity principles; and (5) identification of specific steps to be taken to promote sex equity. Topics of the sessions are: (1) personal attitudes toward sex roles; (2) sex bias in instructional procedures; (3) the teacher, Title IX, and sex equity; (4) nonbiased and affirmative teaching; (5) the origins of bias; (6) institutionalized bias in education; (7) identifying forms of bias in instructional materials; (8) identifying forms of bias in textbook content; (9) distinguishing between biased and nonbiased materials; and (10) summary, evaluation and closing workshop evaluation. Answer sheets to questions raised in the sessions are appended. (JD)
Availability: Title IX Sex Equity Staff, Equal Education Services Unit, Colorado Department of Education, Denver, CO ($5.00).
ERIC Note: This manual was adapted/adopted from the materials prepared for the Council of Chief State School Officers' Title IX Equity Workshops Project by Shirley McCune and Martha Matthews at the Resource Center on Sex Roles in Education, Washington, D.C. (funded by the U.S. Office of Education Women's Program Staff). For the participant workbook, see SP 024 956.
Teachers.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Elementary Secondary Education; Ethnic Bias; Instructional Materials; Media Selection; Nondiscriminatory Education; Sex Bias; Sex Fairness; Sex Stereotypes; Teacher Attitudes; Teacher Influence; Teacher Role; Teacher Workshops; Textbook Bias; Textbook Evaluation; Title IX Education Amendments 1972; Guides, Classroom -- Teacher